Fear of crime in urban parks based on different levels of concealment, incivilities and human presence / Sreetheran Maruthaveeran, Arne Arnberger, Cecil Konijnendijk van den Bosch - Maruthaveeran, Sreetheran; Arnberger, Arne; van den Bosch, Cecil Konijnendijk (2018)
This study examined the effects of concealment, incivilities and presence or absence of people recreating (social cues) on evoking fear of crime in urban parks of Kuala Lumpur. 669 respondents from five parks rated their fear of crime to 12 manipulated photographic representations of a park trail. These results suggest that social and environmental cues may jointly affect fear experiences. From this study the photo with high concealment, with disorder and without people rated the most feared (M=5.86; SD = 1.345) and the photo with low concealment, without disorder and with the presence of people considered the least feared (M=1.85; SD= 1.327). As the level of concealment increases the mean value of fear of crime does increase. This is true either with or without the presence of people or with and without the presence of disorder. It also shows that photos under the condition without people but with the presence of disorder scored the highest mean value compared to other conditions. This shows that the presence of disorder with the absence of people evokes more fear than those photos without the presence of people and disorder. Contrarily, as the level of concealment increases, photos under the condition with people but without the presence of disorder scored the lowest level of fear.